Anaplastic thyroid cancer: how far can we go? - Amaral, Mariana (2020)
Globally, thyroid cancer accounts for 2 % of all cancer diagnoses, and can be classified as well-differentiated or undifferentiated. Currently, differentiated thyroid carcinomas have good prognoses, and can be treated with a combination of therapies, including surgical thyroidectomy, radioactive iodine therapy and hormone-based therapy. On the other hand, anaplastic thyroid carcinoma, a subtype of undifferentiated thyroid carcinoma characterized by the loss of thyroid-like phenotype and function, does not respond to either radioactive iodine or hormone therapies. In most cases, anaplastic thyroid carcinomas are diagnosed in later stages of the disease, deeming them inoperable, and showing poor response rates to systemic chemotherapy. Recently, treatment courses using multiple-target agents are being explored and clinical trials have shown very promising results, such as overall survival rates, progression-free survival and tumor shrinkage. This review is focused on thyroid carcinomas, with particular focus on anaplastic thyroid carcinoma, exploring its undifferentiated nature. Special interest will be given to the treatment approaches currently available and respective obstacles or drawbacks. Our purpose is to contribute to understand why this malignancy presents low responsiveness to current treatments, while overviewing novel therapies and clinical trials.